Decoding the Perpetuation of Patriarchal Culture in the Barbie Movie - Myisha, Nabila; Sabila, Dinda; Maharani, Angelia Brigita; Ramadhan, Akira Hilal; Kamalia, Mirza Fathima Jauhar (CV. Era Digital Nusantara, 2023)
This research aims to analyze the representation of patriarchal culture in the Barbie film through a semiotic study that uses Roland Barthes’ theory. Roland Barthes developed semiotic theory into three parts, namely denotation, connotation, and myth, but in this study, the researchers only utilized connotation and denotation. This research uses a descriptive qualitative method. The data was taken from the scenes and script of the Barbie 2023 film. The researchers collected data by watching the film, observing the characters in every scene and the script, then taking some notes to categorize the semiotic symbols based on Roland Barthes' theory and analyzing the research data. The results of this research show that despite the movie